A fission-yeast gene encoding a protein with features of protein-tyrosine-phosphatases. - Ottilie, S (1991)
Degenerate oligonucleotide probes encoding sequences conserved among mammalian protein-tyrosine-phosphatases (PTPases) were used to amplify DNA fragments from a Schizosaccharomyces pombe cDNA library by polymerase chain reaction (PCR) methods. A cloned PCR product predicted peptide sequences similar to those found in PTPases but not identical to any published sequences. A S. pombe gene, designated pyp1+, was identified in a cDNA library with this PCR probe, cloned, and sequenced. The sequence of the gene predicted a 550-amino acid protein with Mr 61,586, which includes amino acid sequences that are highly conserved in mammalian PTPases. Disruption of the pyp1+ gene resulted in viable cells. Overexpression of the pyp1+ gene in S. pombe permitted detection of a protein of apparent Mr 63,000.